Sustainable supply chain management: decision models for transformation and maturity - Reefke, Hendrik; Sundaram, David (Elsevier, 2018)
Academics and practitioners have realized that supply chains with their many interactions and impacts have to be investigated in order to meet corporate sustainability imperatives. Research has thus far offered only limited theoretical guidance while practical applications often lack a systematic approach. The realization of sustainability goals is impeded by disconnects between supply chain vision, strategy, and execution. This research bridges this gap and offers guidance through the identification and description of influential factors and decision models. An exploratory Delphi study involved supply chain and sustainability experts with the goal to explore and propose factors and decision processes for sustainable supply chain management. This study builds upon the insights offered by seminal models and leverages the Delphi mechanisms of exploration and controlled feedback in order to design, refine, and validate decision models through three consecutive rounds. This Delphi facilitated the identification and assessment of vital relationships and influential factors for sustainable supply chain management. The study culminates in the design and validation of models specifically targeted at the transformation and on-going maturity development of sustainable supply chains. The combination of research outcomes provides targeted decision support to supply chain managers which is desperately needed in order to drive sustainability development and implementation. The main contributions of the study thus are (1) the design of prescriptive artefacts that describe relationships in SSCM, (2) to offer targeted and evaluated decision support functionalities for sustainable supply chains, and (3) to provide fertile ground for future research enquiries.
Keywords: Supply chains; Sustainability; Delphi; Decision models; Maturity; Transformation